'The Power Loom' - Weavers' Circular, 1944 (Lancashire, 1944)
1944 1939-1945 "'The Power Loom' - Weavers' Circular, 1944" [HFR0069], 1944 The Power Loom, a circular report to members from the Nelson and District Weavers Association. This issue includes articles on post war reconstruction of the cotton textile industry and safety [there were 49 deaths in cotton mills during January - March 1944].